Risk factors of constipation in children - Dyah Kurniati Dyah Kurniati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Despite it is not considered as a dangerous situation in children older than 2 years old, but attention is important in young infant. Improper treatment in constipation may contributed to the raise of anxiety, emotionally disorder either for the children or its relatives.Objective: To determine risk factors related to constipation in children.Design and Methods: A case control study was conducted for all of children who were admitted to ambulatory polyclinic and inpatient clinic of Sardjito Hospital during January 2001 - December 2001. A questionnaire was obtained by the researcher or assistant by direct interview to parent or guardian.Results: We enrolled 86 children, consisted of 43 children in constipation group and the43 children as control. There was significant  difference (p  < 0.01) between two groups in the presence of the symp-toms (abdominal pain, pain during defecation, vomit, decrease of appetite and encopresis). More childrenin constipation group and significant difference (p<0.01) when reported having toilet training distur- bance, daily fluid intake, the variety of daily meals (vegetables, fruits) and sweetened foods. Relative risk of having constipation due to toilet training disturbance in constipations group is 0.14 (CI:  0.06 - 0.38).Conclusion: Toilet training disturbance, daily fluid intake, the variability of daily meals and sweetened foods are risk factors of constipation in childhood.Key words: children - constipation - clinical findings- risk factors